An Extrafollicular Adenomatoid Odontogenic Tumor Mimicking a Periapical Cyst - Farzaneh Mosavat; Roxana Rashtchian; Negar Zeini; Daryoush Goodarzi Pour; Shabnam Mohammed Charlie; Nazanin Mahdavi (Case Reports in Radiology)
Adenomatoid odontogenic tumor (AOT) is a rare noninvasive odontogenic tumor that occurs mostly in the second decade of life. Based on its tooth association, AOT can be classified into three categories of follicular, extrafollicular, and peripheral types; the follicular classification is considered as the most common type of AOT. This study reported a large extrafollicular case of AOT in a 40-year-old female. She was asymptomatic and tumor was detected accidentally by her dental practitioner. Since the panoramic radiograph showed a well-defined unilocular radiolucent lesion, we observed radiopaque spots within the lesion by using cone beam computed tomography. The extrafollicular type can mimic a periapical radiolucent lesion.